Assessment of energy demand in the new Olympic windsurf board: Neilpryde RS:X - Castagna, O.; Vaz Pardal, M. C.; Brisswalter, J. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
The aim of this study was to evaluate the energy demands f sailing the new Neilpryde RS:X R Olympic windsurf board. Ten skilled male subjects performed an exhausted incremental treadmill test to determine their maximal physiological parameters. Thereafter, four tests in a randomed order were performed using two wind conditions, light [2 to 4 ms-1 (4 to 8 knots)] and strong: [9 to 11 ms-1(16 to 22 knots)]. Oxygen consumption (V.O2, ml.min-1.kg-1), blood lactate concentration ([la]b,mmol.l-1), and time spent for pumping (% total time) were recorded during 10 minutes of up-wind leg and during 6 minutes of down-wind leg. Results indicate that sailing on RS:X is associated with a high level of energy demand using both aerobic and anaerobic pathways whatever the wind conditions. During downwind leg, V.O2 (ml.min-1.kg-1), [la]b (mmol.l-1) and time spent for pumping (% total time) values were for the light and strong wind conditions, 56.5 + 5.9 vs. 55.5 + 3.6; 10.2 + 1.5 vs. 9.6 ± 2.3 and 69 ± 5 % vs. 64 ± 2 %, respectively. In contrast, during up-wind leg the same parameters for light and strong wind were 53.9 + 4.5 vs. 40.4 + 7.2; 9.7 + 2.8 vs. 5.0 + 2.7 and 66 + 3 % vs. 37 + 8 %, respectively. During up-wind leg with strong wind conditions less time was spent in pumping (p<0.05), mean oxygen consumption values were close to 60% V.O2max, and post exercise blood lactate was lower than 50% maximal lactate concentration. These results could be related to the time spent in pumping action, involving the whole body activity When sailing with the RS:X board, physiological demand seems to be higher than with the previous official Olympic windsurf board (Mistral One Design R (MOD)). This difference could be mainly attributed to the specific biomechanical constraints induced by each board characteristics.